When are breast cancer patients old enough for the quitclaim of local control? - Sautter-Bihl, Marie-Luise; Wenz, Frederik (Strahlentherapie und Onkologie, 2012)
BackgroundAlthough postoperative radiotherapy (RT) after breast-conserving surgery (BCS) halves the 10-year recurrence rate in breast cancer patients through all age groups, the question of whether RT may be omitted and replaced by endocrine therapy for women aged 70 years and older with low-risk factors has recently become an issue of debate.MethodsSurvey of the relevant recent literature (Medline) and international guidelines.ResultsThree randomized studies investigating the effect of RT in older women revealed significantly increased local recurrence rates when RT was omitted, and a negative impact on disease-free survival was observed in two of these trials. Despite these findings, in one of the studies omission of RT in women over 70 is recommended, leading to a respective amendment in the guidelines of the American National Comprehensive Cancer Network. Several large retrospective cohort studies analyzing the outcome of patients over 65 years with and without RT have since been published and showed a significantly improved local control in all subgroups of advanced age and stage, which predominantly translated into improved disease-free and overall survival.ConclusionNo subgroup of elderly patients has yet been identified that did not profit from RT in terms of local control. Therefore, chronological age alone is not an appropriate criterion for deciding against or in favor of adjuvant RT. The DEGRO breast cancer expert panel explicitly discourages determination of a certain age for the omission of postoperative RT in healthy elderly women with low-risk breast cancer. For frail elderly women, treatment decisions should be individually decided on the basis of standardized geriatric assessment.
Gesehen am 12.07.2018